Investigation of Temperature Field Evolution in Pangasius Fillets during Freezing - Hoang Thi Nam Huong; Do Huu Hoang (Engineering Science Letter, 2026)
This study investigates the spatial and temporal evolution of temperature within Pangasius fillets during freezing using a finite element model of two-dimensional nonlinear transient heat conduction with phase change and convective boundary conditions. The model was implemented in ANSYS for a representative fillet cross-section and simulated under an air temperature of −40 °C and air velocity of 10 m/s. Temperature histories at 25 representative nodes were analyzed to characterize local freezing behavior and identify differences between surface and interior regions. The results reveal three characteristic stages: rapid precooling toward 0 °C, a phase-change period dominated by latent heat release, and subsequent sensible cooling after freezing is completed. Surface and corner regions cooled substantially faster than interior locations because of stronger convective heat transfer, while the geometric center exhibited the longest freezing delay. The maximum thermal delay between the corner and center occurred near −3 °C, reaching approximately 800 s, and decreased as the temperature approached the fully frozen state. Below approximately −18 to −20 °C, temperature-time curves exhibited increasingly similar slopes, indicating completion of phase change. These findings demonstrate that temperature-field analysis can support reliable freezing-time prediction and provide a quantitative basis for optimizing operating conditions, energy efficiency, and product quality.